Digital Learning Innovation Through an Interdisciplinary Approach - Jonathan David Miller; Anna Katharina Schneider (CV JK Riset Publishing Group, 2025)
Digital learning innovation is often hampered by an overly technocentric approach that neglects the human dimension. This study aims to analyze the effectiveness of an interdisciplinary approach in encouraging holistic digital learning innovation in Indonesia. The research method used was a systematic literature review by analyzing 40 articles from Sinta and ISSN-accredited journals for the 2023–2025 period. The results show that integrating cognitive psychology and pedagogical design can increase student learning retention by up to 20%, while an educational economics perspective ensures the efficiency of technology investments in schools. The discussion highlights that without legal protection of personal data and ergonomic principles, digital innovation risks triggering user resistance and physical health problems. The study's conclusions emphasize that synergy across disciplines—pedagogy, technology, sociology, and law—is an absolute prerequisite for the sustainability of digital transformation in education. The research recommendations are directed at strengthening student data governance policies and interdisciplinary teacher training to maximize the impact of technology in the classroom.